Gender inequality and its impact on economic growth: a study of the relationship between gender inequality in employment, education and growth in South Africa - Ruiters, Michele (Research of GSB, 2019)
This thesis explores the impact that gender equality in employment and education in South Africa has on the country’s Gross Domestic Product (GDP) growth on a quarterly basis from 2008 – 2017. The hypothesis is that gender equality in employment and education will impact economic growth in South Africa because the inclusion of women as economically active and educated equals will have a direct impact on the economy. The Autoregressive Distributive- Lag (ARDL) model is used to quantify the long run relationships between the dependent (economic growth) and independent (women’s employment and education levels) with Granger causality tests used to examine short-run causal relationships between the variables. The study discovered that women’s employment and the combined variable of women’s education and employment have an impact on GDP growth. However, women’s education does not have a significant impact on economic growth. It is also found that women’s employment has an impact on women’s education but the reverse does not hold. The results from this study inform employment and education policy in South Africa and ensure that women and men have equal access to labour markets and schooling. The objective is to facilitate the equal contribution of men and women to economic growth.